DETERMINATION OF ENVIRONMENTAL SUSTAINABILITY AND ANTROPOGENIC LOADING IN THE TERRITORY OF THE AMALGAMATED COMMUNITY - Aleksandra KOSTYSHIN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In the classical sense, benchmarking is the most effective way to find hidden production reserves through a comparative analysis of production and economic indicators of farms (agricultural enterprises) in the industry. It allows you to determine your strengths and weaknesses; to identify those methods of work that need to be improved; compare your achievements with competitor performance; improve business processes and product quality, increase efficiency, reduce costs, etc. In this article by the method of benchmarking was determined the economic feasibility of keeping Lebedynska breed of dairy cows, despite the small amount of livestock. The calculations confirmed the economic feasibility of keeping the Lebedynska breed of dairy cows compared with other more common breeds of dairy cows, taking into account biologically-selective features. In the total cost of milk over 50% is the cost of forage. Therefore, to calculate how profitable is the milk production, it is worth to determine how many kilograms of milk we get from 1 kg of dry matter of forage. Among our calculations, the highest conversion rate of dry matter of forage (1.42-1.44) have Holstein, Ukrainian brown and Ukrainian black-pinto breeds, and the smallest has Ukrainian red-pinto breed (1.18). Lebedynska breed has an index of 1.28. It is very clear: increasing productivity will increase the efficiency of forage conversion and farm profitability. But important factor for the efficiency of forage conversion is the improvement of roughage quality. Productivity of cows has a direct dependence on feeding: Holstein breed has 31.9 kg of milk yield per day (fat 3.84%, protein 3.28%); Lebedynska - 25.1 kg per day (fat 3.8%, protein 3.43%). The structure of the cow ration determines the forage costs (the cost of a feed-day). The highest forage costs have the farms where the concentrated feed is dominated by the structure of ration. It's the farms holding the Holstein breed - 191.7 UAH (by feeding 20.5 kg of grain per day per cow), the smallest - 82 UAH - farms holding the Ukrainian brown (4.3 kg grain per day per cow). In the structure of the diet of Lebedynska breed cows, grains contain 8.5 kg, and the cost of the feed-day is 100.3 UAH.